The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1182/bloodadvances.2022009389
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of ibrutinib plus R-CHOP in untreated DLBCL coexpressing BCL2 and MYC in the phase 3 PHOENIX trial

Abstract: Diffuse large B-cell lymphoma (DLBCL) with high co-expression of BCL2 and MYC proteins (double-expressor [DE] lymphoma), is considered an adverse prognostic indicator associated mostly with non-germinal center B-cell-like (non-GCB) DLBCL. BCL2/MYC overexpression is associated with B-cell receptor (BCR) pathway activation and, consequently, DE DLBCL may be sensitive to BCR inhibitors. We assessed whether high BCL2/MYC co-expression by RNA sequencing could identify a patient subset responsive to ibrutinib using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…An easy-to-use IHC biomarker or gene expression signature could allow for widespread adoption in the clinic, particularly within the community setting. Moreover, a recent retrospective analysis has also demonstrated that non-GCB DLBCLs with high MYC and BCL2 mRNA expression also benefit from the addition of ibrutinib to R-CHOP, 39 which further supports the notion that transcriptional profiling can effectively enrich for responsiveness to BTKi-based regimens in DLBCL.…”
Section: Discussionmentioning
confidence: 67%
“…An easy-to-use IHC biomarker or gene expression signature could allow for widespread adoption in the clinic, particularly within the community setting. Moreover, a recent retrospective analysis has also demonstrated that non-GCB DLBCLs with high MYC and BCL2 mRNA expression also benefit from the addition of ibrutinib to R-CHOP, 39 which further supports the notion that transcriptional profiling can effectively enrich for responsiveness to BTKi-based regimens in DLBCL.…”
Section: Discussionmentioning
confidence: 67%
“…In the Phoenix clinical trial, the 3-year OS and PFS in the intent-to-treat population treated with ibrutinib plus R-CHOP were 85.8% and 70.8%, respectively [ 21 ]. Compared to the Phoenix study, the performance status of the patients in this study was worse (ECOG = 2, 42.1% vs. 9.1%), with an increase in the proportion of patients with BM involvement (21.1% vs. 11.9%), DEL involvement (57.9% vs. 43.6%) [ 37 ], extranodal involvement ≥ 2 (47.4% vs. 31%), and IPI 3–5 (57.9% vs. 43.6%). Due to the limited number and the heterogeneity of patients in this research, the OS and PFS of the non-GCB group were lower than in the Phoenix study.…”
Section: Discussionmentioning
confidence: 72%
“…In the phase 3 PHOENIX trial, DEL patients receiving ibrutinib plus R-CHOP had comparable OS (HR: 1.042, 95%CI: [1.708–1.534], P = 0.8338) and EFS (HR: 0.987, 95%CI: [0.608–1.601], P = 0.9573) to non-DEL patients. Moreover, ibrutinib plus R-CHOP increased EFS and OS in patients younger than 60 years old with DEL compared to R-CHOP, but there was no significant difference in older patients [ 37 ]. BTKi have shown potential benefits in the treatment of DEL patients, but further research is needed to discover its specific mechanism toward DEL, and whether they might aid older DEL patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was also associated with more frequent adverse events (e.g., febrile neutropenia) 58 . Post‐hoc gene expression analysis of tumor samples revealed superior EFS and OS in patients <60‐years‐of‐age with DEL, MCD and N1 non‐GCB disease 59 . Similarly, in the single‐arm phase II IVORY trial of 24 patients with EBV+ DLBCL, I‐RCHOP yielded a more favorable CR in patients <65‐years‐old relative to matched cases treated with R‐CHOP (87% vs. 69%) 60 .…”
Section: Frontline Therapymentioning
confidence: 99%